Enhancement of the lepton flavor violating Higgs boson decay rates from SUSY loops in the inverse seesaw model - Arganda Carreras, Ernesto (2016)
In this article, we study the full one-loop SUSY contributions to the lepton flavor violating Higgs decay h→τμ¯, within the context of the supersymmetric inverse seesaw model. We assume that both the right-handed neutrino masses, MR, and their supersymmetric partner masses, mνR, are not far from the interesting O(TeV) energy scale, and we work with scenarios with large neutrino Yukawa couplings that transmit large lepton flavor violating effects. By exploring the behavior with the most relevant parameters, mainly MR, mνR and the trilinear sneutrino coupling Aν, we will look for regions of the parameter space where the enhancement of BR(h→τμ¯) is large enough to reach values at the percent level, which could explain the excess recently reported by CMS and ATLAS at the CERN Large Hadron Collider.